Women in the Bible, Qumran and Early Rabbinic Literature - Heger, P. (Studies on the Texts of the Desert of Judah, 2014)
Women in the Bible, Qumran and Early Rabbinic Literature: Their Status and Roles explores the different attitudes toward the woman